High dose efficiency atomic resolution imaging via electron ptychography - Pennycook, TJ; Martinez, GT; Nellist, PD; Meyer, JC (Elsevier, 2018)
Radiation damage places a fundamental limitation on the ability of microscopy to resolve many types of materials at high resolution. Here we evaluate the dose efficiency of phase contrast imaging with electron ptychography. The method is found to be far more resilient to temporal incoherence than conventional and spherical aberration optimized phase contrast imaging, resulting in significantly greater clarity at a given dose. This robustness is explained by the presence of achromatic lines in the four dimensional ptychographic dataset.